Время доверять: [роман] / Гера Фотич - Фотич Гера (Любимый детектив, 2018)
Экземпляры: аб. Центральная библиотека (20190606) / Инвентарный номер: 6789 / Цена: / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: Ф 81 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=411.2)6